Cabozantinib: an orphan drug for thyroid cancer. (2nd December 2015) - Viola, D.; Cappagli, V.; Matrone, A.; Mazzeo, S.; Elisei, R.
Abstract : Introduction : Until recently, no therapeutic options were available for the treatment of advanced medullary thyroid cancer (MTC). Cabozantinib (XL184) is a novel tyrosine kinase inhibitor (TKI) that inhibits several tyrosine kinase receptors, in particular those coded by MET, VEGFR-2 and RET oncogenes that are considered to be involved in the pathogenesis of MTC. Areas covered : This article provides an overview of the phase I and III trials that demonstrated the efficacy of cabozantinib in two cohorts of advanced MTC patients who were naïve or previously treated with other TKIs. The benefits in terms of progression-free survival (PFS), overall survival (OS) and the demographic clinical and mutational status of the two cohorts of MTC patients are reported and discussed. Expert opinion : The possibility to have a therapeutic option for the treatment of patients with advanced and progressive MTC and, in particular, the evidence that the drug can be active also in those patients who already experienced disease progression while taking another TKI is a great opportunity as demonstrated in cases treated with cabozantinib after vandetanib such as the one reported in this paper.